Bone Morphogenetic Protein Signaling Protects against Cerulein-Induced Pancreatic Fibrosis - Gao, Xuxia (Public Library of Science, 2014)
Bone morphogenetic proteins (BMPs) have an anti-fibrogenic function in the kidney, lung, and liver. However, their role in chronic pancreatitis (CP) is unknown. The aim of this study was to define the anti-fibrogenic role of BMP signaling in the pancreas in vivo under CP induction. Mice with a deletion of BMP type II receptor (BMPR2(+/−)) were used in this study in comparison with wild-type mice. CP was induced by repetitive cerulein injection intraperitoneally for 4 weeks, and the severity of CP was evaluated. Pancreatic stellate cells (PSCs) were isolated from the mice and treated with BMP2 and TGF-β in vitro, and extracellular matrix protein (ECM) production was measured. Smad and mitogen-activated protein kinase (MAPK) signaling was also evaluated. BMPR2(+/−) mice revealed a greater pancreatic fibrosis, PSC activation and leukocyte infiltration after CP induction compared to wild-type mice (P<0.05). Under CP induction, phospho (p)Smad1/5/8 was elevated in wild-type mice and this effect was abolished in BMPR2(+/−) mice; pSmad2 and pp38(MAPK) were further enhanced in BMPR2(+/−) mice compared to wild-type mice (P<0.05). In vitro, BMP2 inhibited TGF-β-induced ECM protein fibronectin production in wild-type PSCs; this effect was abolished in BMPR2(+/−) PSCs (P<0.05). In BMPR2(+/−) PSCs, pSmad1/5/8 level was barely detectable upon BMP2 stimulation, while pSmad2 level was further enhanced by TGF-β stimulation, compared to wild-type PSCs (P<0.05). BMPR2/Smad1/5/8 signaling plays a protective role against cerulein-induced pancreatic fibrosis by inhibiting Smad2 and p38(MAPK) signaling pathways.